Harmonization of Funding for Government Cooperation With Small-Scale Public-Private Partnership - Kurdi, Kurdi; Amalia, Prita; Mahardhito Adhitya Wardhana, Yuki (Jurnal Ius Constituendum, 2024)
This study examines the relevance of the Ministry of National Development Planning (Bappenas) Regulation No. 7 of 2023 and Law No. 1 of 2022 in supporting the Small-Scale Public-Private Partnership (PPP) scheme. The urgency of this research lies in the need to improve existing regulations and ensure legal certainty for Small-Scale PPPs, as these regulations provide relevant frameworks for such schemes. The study aims to understand how regulatory harmonization can enhance regional fiscal capacity and facilitate project implementation. Utilizing a normative juridical method with legislative and conceptual approaches, the study finds that since 2015, only 6 out of 34 PPP projects involved local governments. The conclusion highlights the importance of simplifying regulations and adjusting project value requirements to increase regional participation and fiscal effectiveness. The study recommends regulatory adjustments to support more equitable and sustainable infrastructure development.